Epicentre to aftermath: rebuilding and remembering in the wake of Nepal's earthquakes - Hutt, Michael; Liechty, Mark; Lotter, Stefanie (Cambridge University Press, 2021)
Epicentre to Aftermath makes both empirical and conceptual contributions to the growing body of disaster studies literature by providing an analysis of a disaster aftermath that is steeped in the political and cultural complexities of its social and historical context. Drawing together scholars from a range of disciplines, the book highlights the political, historical, cultural, artistic, emotional, temporal, embodied and material dynamics at play in the earthquake aftermath. Crucially, it shows that the experience and meaning of a disaster are not given or inevitable, but are the outcome of situated human agency. The book suggests a whole new epistemology of disaster consequences and their meanings, and dramatically expands the field of knowledge relevant to understanding disasters and their outcomes.
Title from publisher's bibliographic system (viewed on 08 Jul 2021)
Keywords: Nepal -- Social conditions -- 21st century; Nepal -- Politics and government -- 21st century; Konferenzschrift -- 2019 -- London; Wiederaufbau; Geschichte 2015; Erdbeben; Nepal